Peningkatan Pengamanan Data File Menggunakan Algoritma Kriptografi AES Dari Serangan Brute Force - Indra Gunawan Indra (Jurnal Media Informatika, 2023)
Abstract− Data is a component that can be collected into a single unit and managed, so that it can be used as useful information. Any information that has been collected will later be stored in digital form in the form of files that can then be managed in such a way before the file is published. By using information into the form of files, it can save more than the use of paper types. However, along with the times, the use of digital files has a level of security that is starting to be risky because there are often data breaches from parties who do not have the right to use data. Some of the methods used for data breaches are to use brute force methods. So to be able to anticipate the data breach, several methods are needed that can be used to secure data, including using cryptography with the AES (Advanced Encryption Standard) method. With the use of this method, it is hoped that at least it can increase the security of file data used and stored in digital archives.